SOCIAL WORK IN THE RURAL AREA FROM DOLJ COUNTY, ROMANIA - Sorescu, Emilia-Maria (European Scientific Journal, ESJ, 2015)
After 40 years of communism and after other 25 years without communism, the social work in Romania tries yet to take back its place. A foray into the history of the modern social work in Romania illustrates the rupture brought by the intrusion of the political regime in the evolution of the social work profession and the difficulty of the rebuilding its identity in this country. The rural area is the most affected by this situation, so the article includes the results of an evaluation aiming the communication skills of the people who have responsibilities as social worker according to the job description, but they are not qualified social workers. This research was conducted in 2013 in about a third of the rural localities from Dolj County. The analysis of the relevant legislation, of the statistical information on the present situation of the qualified social workers in the rural areas and the interpretation of the findings of this research led us to the conclusions that suggest the need for major improvement of the state of facts.